Explorasi Faktor Penghambat Pengembangan Daya Tarik Pantai Arta Indah di Kabupaten Padang Pariaman - Fatimah Az-Zahra; Hendri Azwar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the Inhibiting Factors for the Development of the Arta Indah Beach Tourist Attraction in Padang Pariaman Regency. With indicators of damaged road access, public toilets and abandoned gazebo facilities. In addition, this study aims to explain the obstacles in the Development and Role of the Community in the Development of the Arta Indah Beach Tourist Attraction in Padang Pariaman Regency. This type of research is qualitative research using descriptive methods, for research informants the author uses Purposive sampling while for data collection techniques the author uses observation, interviews, and documentation studies.Based on the results of the study it was stated that 1) The attractions of Arta Indah Beach include a clean beach, has rows of pine trees, and a beautiful sunset event 2) The inhibiting factors for Arta Indah Beach tourism are less than optimal road access, inadequate toilets and many facilities that have been damaged and obsolete 3) the role of the local community is still less effective, especially in the quality of human resources in understanding the management of tourist villages. The hope for the future is that the government and the Arta Indah Beach community will be able to improve the lacking facilities and pay attention to the tourist attractions on Arta Indah Beach.